2006
DOI: 10.1261/rna.55406
|View full text |Cite
|
Sign up to set email alerts
|

The network of protein–protein interactions within the human U4/U6.U5 tri-snRNP

Abstract: The human 25S U4/U6.U5 tri-snRNP is a major building block of the U2-type spliceosome and contains, in addition to the U4, U6, and U5 snRNAs, at least 30 distinct proteins. To learn more about the molecular architecture of the tri-snRNP, we have investigated interactions between tri-snRNP proteins using the yeast two-hybrid assay and in vitro binding assays, and, in addition, have identified distinct protein domains that are critical for the connectivity of this protein network in the human tri-snRNP. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
212
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(230 citation statements)
references
References 57 publications
8
212
0
10
Order By: Relevance
“…hPrp3p presumably plays an important role in recruiting other splicing factors like hPrp4p to the U4/U6 small ribonucleoprotein and docking the U4/U6/U5 tri-snRNP to the prespliceosome (Liu et al, 2006). In the present study we describe that hPrp3p interacts with protein kinase CK2 in vitro and in vivo and that is phosphorylated by this kinase.…”
Section: Introductionmentioning
confidence: 52%
“…hPrp3p presumably plays an important role in recruiting other splicing factors like hPrp4p to the U4/U6 small ribonucleoprotein and docking the U4/U6/U5 tri-snRNP to the prespliceosome (Liu et al, 2006). In the present study we describe that hPrp3p interacts with protein kinase CK2 in vitro and in vivo and that is phosphorylated by this kinase.…”
Section: Introductionmentioning
confidence: 52%
“…A number of proteins essential for different steps of splicing interact with the C-terminal cassette of Brr2 (24,25). The ability of the C-terminal cassette to transmit signals to the N-terminal cassette suggests that these proteins may not merely use the C-terminal cassette as a passive landing pad but also to influence the N-terminal cassette from a distance.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports speculated that HAT repeats might bind RNA (1,5,7). However, a lack of evidence for RNA binding and the fact that some HAT repeats can bind peptides (8,9) have led recent literature to assume that HAT motifs serve only to support protein-protein interactions (3, 9, 10). Our demonstration that the HAT protein HCF107 binds RNA with high affinity and sequence specificity together with the exclusive association of HAT proteins with RNA-containing complexes strongly suggest that RNA binding activity contributes to the biological functions of most HAT domains.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of CstF-77 confirmed that HAT repeat tracts adopt a TPR-like structure (3, 4). The possibility that HAT repeat tracts might bind RNA has been suggested (1, 5-7), but the notion that HAT repeat tracts serve as a scaffold for binding other proteins dominates recent literature (3,(8)(9)(10)). This view is reflected by the annotation of the HAT motif at InterPro, which states only that "the repeats may be involved in protein-protein interactions" (http://www.ebi.…”
mentioning
confidence: 99%